EFFECT OF THE COMPLEX PROBIOTIC ON LIPID METABOLISM AND OXIDATIVE STRESS AFTER POISONING WITH NICKEL AGAINST THE BACKGROUND OF EXPERIMENTAL ATHEROSCLEROSIS - Ibragimov, R.I. (World of Medicine and Biology, 2025)
The work studied the effect of the complex probiotic on the state of lipid metabolism and oxidative stress in white male rats after poisoning with nickel nitrate against the background of experimental atherosclerosis. After modeling atherosclerosis, rats were exposed to nickel nitrate for 30 days. In the experimental group, a month after poisoning, the animals received the complex probiotic, which was added to the drinking water of the drinkers for a month. It was found that when male rats were chronically poisoned with nickel nitrate after modeling atherosclerosis, there was a progressive increase in lipid metabolism disorders and oxidative stress processes. The use of a complex probiotic after poisoning with nickel nitrate improved lipid metabolism and oxidative stress. The obtained data show the important practical significance of probiotics in the treatment of nickel poisoning, especially in patients with atherosclerotic vascular damage.
Keywords: atherosclerosis; lipid metabolism; oxidative stress; nickel; complex probiotic